Moderating effect of perceived risk on the relationship between product safety and intention - Ismail, Sarina; Mohd Mokhtar, Sany Sanuri (Growing Science, 2015)
Herbal Products industry has experienced significant growth in product demand.Therefore, this study aims to identify the factors effecting the actual buying of Herbal Product.This study also examines the moderation effect of perceived risk on the relationship between product safety and intention. Mall intercept survey was used to collect data from six various states in Malaysia.The data is analyzed using Partial Least Squares (PLS) path modeling. The path coefficient results supported the direct influence of intention on actual buying. Similarly, the findings reveal that perceived risk moderate the relationship between product safety and buying intention.